The Post of Pluralism: Religious Pluralism in the Practical Areas of Indonesia - M. Adib Fuadi Nuriz; Jaffary Awang (Universitas Darussalam Gontor, 2018)
The recent research of religious pluralism concludes that religious pluralism is basically originality from relativism to the equality of religions. This terminology presents to avoid the concept of the Truth Claim of religions. In the contemporary times, religious pluralism figures in Indonesia continue to develop religious pluralism from theological into practice. Due to the impact of pluralism on religiosity and social problem, it is necessary to analyze how pluralism may emphasis practical areas of Muslim community. The investigation focuses on discourses of mainstreaming religious pluralism in Islamic Higher Education Institution in Indonesia, maintaining dialogue and religious tolerance based on pluralism, building of tolerance, inclusivism, and multiculturalism. This research concludes that the two main institutions with more influences of religious pluralism are State Islamic University of Syarif Hidayatullah Jakarta (UIN Jakarta) and Sunan Kalijaga State Islamic University of Yogyakarta (UIN Yogyakarta). These two institutions assumed have succeeded on building of pluralism and the society based on some approaches; by mainstreaming of religious pluralism among Muslim scholars in every level and building of religious dialogue and tolerance based on pluralism. In order to strength the movement of religious pluralism UIN Jakarta and UIN Yogyakarta dedicated to cooperate with several institutions; cooperation with local universities and abroad universities, join program and cooperation with non-governmental organizations in the development of inter religious studies. Therefore, this research finds out post religious pluralism as the discourses of practical areas of pluralism itself.